The impact of electoral systems upon the behaviour of members of parliament - Mjekiqi, Shqipe (Trinity College (Dublin, Ireland). Department of Political Science, 2015)
This thesis examines the impact of electoral systems on the way Members of Parliament (MPs) behave as measured both in terms of Parliamentary Party Group (PPG) unity and constituency links. The main argument is that electoral systems are likely to have a greater impact on MPs’ behaviour in newly-democratised countries that have weak Party System Institutionalisation (PSI) than in established parhamentary democracies that have high levels of PSI. In weak PSI countries, I argue, electoral systems that allow intra-party competition are likely to lead to lower PPG unity and stronger constituency links, while electoral systems that lack intra-party competition are likely to lead to higher PPG unity and weaker constituency links.
Keywords: Political Science, Ph.D.; Ph.D. Trinity College Dublin